2022
DOI: 10.1055/a-1872-0613
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pharmacokinetic Gene Variation on Therapeutic Drug Levels and Antidepressant Treatment Response

Abstract: Introduction Pharmacogenetic testing is proposed to minimize adverse effects when considered in combination with pharmacological knowledge of the drug. As yet, limited studies in clinical settings have investigated the predictive value of pharmacokinetic (pk) gene variation on therapeutic drug levels as a probable mechanism of adverse effects, nor considered the combined effect of pk gene variation and drug leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 49 publications
1
14
3
2
Order By: Relevance
“…In addition to the studies that were included by the 2015 meta-analysis, except for Uhr et al 20 and Dong et al 37 we added new data from the CAN-BIND-1 and IRL-GREY, 30 and from 3 other studies published after 2016. 31,56,57 Our analyses of the other five ABCB1 SNPs (rs1045642, rs2032582, rs2032583, rs2235015, and rs2235040) did not reveal significant associations with any of the examined antidepressant treatment outcome variables in outpatients. These negative findings in outpatients remain consistent with meta-analysis by Breitenstein et al 23 who reported a significant association between rs2032583 and rs2235015 and antidepressant treatment outcomes in inpatients only.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…In addition to the studies that were included by the 2015 meta-analysis, except for Uhr et al 20 and Dong et al 37 we added new data from the CAN-BIND-1 and IRL-GREY, 30 and from 3 other studies published after 2016. 31,56,57 Our analyses of the other five ABCB1 SNPs (rs1045642, rs2032582, rs2032583, rs2235015, and rs2235040) did not reveal significant associations with any of the examined antidepressant treatment outcome variables in outpatients. These negative findings in outpatients remain consistent with meta-analysis by Breitenstein et al 23 who reported a significant association between rs2032583 and rs2235015 and antidepressant treatment outcomes in inpatients only.…”
Section: Discussioncontrasting
confidence: 57%
“…Identification of data through author collaboration. Three datasets included in the systematic review and meta-analyses which were obtained through author collaborations are: STAR*D (Peters et al 17 ), IRL-GREY, 30 and Scherf-Clavel et al 31 The STAR*D (Sequenced Treatment Alternatives to Relieve Depression: NCT00021528) is a multisite clinical study which included participants diagnosed with MDD and received prospective treatment with citalopram for at least 6 weeks. The IRL-GREY (Incomplete Response in Late-Life Depression: Getting to Remission; NCT00892047) sample consisted of adults ≥ 60 years.…”
Section: Systematic Review and Meta-analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Периоды полувыведения у венлафаксина (4-14 ч.) и ODV (10-20 часов) сравнительно короткие -меньше интервала дозирования 24 ч, что требует мониторинга их остаточного уровня, влияющего на выраженность антидепрессивного эффекта [7].…”
Section: введение / Introductionunclassified